Uji Aktivitas Antibakteri Sabun Padat Herbal Terhadap Bakteri Staphylococcus aureus - Putri, Cahaya Kamila; Khoftiah, Jannah; Agusr, Ridha; Farma, Siska Alicia; Advinda, Linda (Prosiding Seminar Nasional Biologi, 2021)
Staphylococcus aureus is an aerobic bacterium that is gram positive and is one of the normal human flora on the skin and mucous membranes. Staphylococcus aureus is the main pathogen in humans and almost everyone has experienced S. aureus infections that vary in severity, from food poisoning to mild to severe skin infections that are life-threatening. Solid bath soap is a skin cleansing preparation to protect the skin from harmful bacteria because it has a special formula. This study aims to determine the antibacterial activity of herbal herbal solid soap using agar diffusion method (Kirby Bauer test) using 5 mm diameter paper discs by calculating the diameter of the inhibition zone against Staphylococcus aureus bacteria. The results showed that the maximum average value of the inhibition zone was 6.66 mm in the treatment with a concentration of 300 mg/ml, and the minimum average value of the inhibition zone was 5.22 mm in the treatment with a concentration of 250 mg/ml. Based on the results of the average value of the inhibition zone, the experiment with a concentration of 300 mg/ml was more effective than other concentrations.